2002
DOI: 10.1182/blood-2002-03-0801
|View full text |Cite
|
Sign up to set email alerts
|

Home care during the pancytopenic phase after allogeneic hematopoietic stem cell transplantation is advantageous compared with hospital care

Abstract: After myeloablative treatment and allogeneic stem cell transplantation (SCT), patients are kept in isolation rooms in the hospital to prevent neutropenic infections. During a 3-year period, patients were given the option of treatment at home after SCT. Daily visits by an experienced nurse and daily phone calls from a physician from the unit were included in the protocol. We compared 36 patients who wished to be treated at home with 18 patients who chose hospital care (control group 1). A matched control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(143 citation statements)
references
References 31 publications
4
137
2
Order By: Relevance
“…Recently van Tiel et al 11 published a review of six studies describing home care vs hospital care of patients with hematological malignancies after HSCT and suggested no benefit for protective isolation environments. In a unique approach Svahn et al (2002), 12 described a model in which treatment at home was provided for allo-HSCT during the pancytopenic phase. This study found home care advantageous compared with hospital care.…”
Section: Introductionmentioning
confidence: 99%
“…Recently van Tiel et al 11 published a review of six studies describing home care vs hospital care of patients with hematological malignancies after HSCT and suggested no benefit for protective isolation environments. In a unique approach Svahn et al (2002), 12 described a model in which treatment at home was provided for allo-HSCT during the pancytopenic phase. This study found home care advantageous compared with hospital care.…”
Section: Introductionmentioning
confidence: 99%
“…Even though this study was not performed to analyze costs for management of hematological patients, the HHS has already demonstrated economical advantages over traditional care in the management of elderly patients affected by stroke or chronic obstructive pulmonary disease (Ricauda et al, 2005;Aimonino Ricauda et al, 2008). The home treatment of patients during the post-transplant pancytopenic phase has been found cheaper than in-hospital treatment (Svahn et al, 2002). Cartoni et al (2007) demonstrated that the mean monthly cost for subjects with hematological illnesses are lower than the average costs that would have been charged to the National Health System in the event of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were kept in reversed isolation or treated at home 24 Between 1995 and 2000, G-CSF was given to 11 UCB patients and to 10 recipients of mismatched unrelated grafts, at a dose of 5 mg per day intravenously from day 10 until neutrophil engraftment 40.5 Â 10 9 /l for 2 days. After that, G-CSF prophylaxis was stopped because we found that it resulted in an increased incidence of acute GVHD of grades II-IV.…”
Section: Supportive Carementioning
confidence: 99%
“…25 Supportive care has been described in detail previously, especially in BM recipients. 20,24 Chimerism analysis PCR amplification of variable numbers of tandem repeats was used to evaluate various degrees of donor and recipient chimerism in CD3 þ , CD19 þ and CD33 þ cells enriched from blood samples using immunomagnetic beads (Dynal, Oslo, Norway), as previously described. 26 Complete donor chimerism (DC) was defined as 495% donor cells.…”
Section: Supportive Carementioning
confidence: 99%